Nifetepimine, a Dihydropyrimidone, Ensures CD4(+) T Cell Survival in a Tumor Microenvironment by Maneuvering Sarco(endo)plasmic Reticulum Ca(2+) ATPase (SERCA) - Ghosh, Swatilekha (American Society for Biochemistry and Molecular Biology, 2012)
Multiple mechanisms have been proposed by which tumors induce T cell apoptosis to circumvent tumor immune-surveillance. Although sarco/endoplasmic reticulum Ca(2+)-ATPase (SERCA) have long been known to regulate intracellular Ca(2+) homeostasis, few studies have examined the role of SERCA in processes of T lymphocyte survival and activation. In this context it remains largely unexplored as to how tumors jeopardize SERCA function to disable T cell-mediated anti-tumor immunity. Here, we show that human CD4(+) T cells in the presence of tumor conditions manifested an up-regulation of SERCA3 expression that resulted in development of endoplasmic reticulum stress leading to CD4(+) T cell apoptosis. Prostaglandin E(2) produced by the tumor cell plays a critical role in up-regulating SERCA3 by enhancing the binding of its transcription factor Sp1. Gene manipulation and pharmacological approaches further established that an increase in SERCA expression also resulted in subsequent inhibition of PKCα and -θ and retention of NFκB in the cytosol; however, down-modulation of SERCA3 expression by a dihydropyrimidone derivative, ethyl-4-(3-nitro)-phenyl-6-methyl-2-oxo-1,2,3,4-tetrahydropyrimidine-5 carboxylate (nifetepimine), protected the CD4(+) T cells from tumor-induced apoptosis. In fact, nifetepimine-mediated restoration of PKC activity resulted in nuclear translocation of p65NFκB, thereby ensuring its survival. Studies further undertaken in a tumor-bearing mice model revalidated the immunoprotective role of nifetepimine. Our present study thus strongly suggests that imbalance in cellular calcium homeostasis is an important factor leading to CD4(+) T cell death during cancer and holds promise that nifetepimine may have the potential to be used as an immunorestoring agent in cancer bearers.